Analysis of approaches to creating a geodatabase for GIS monitoring surface water quality - Зацерковний, В.І.; Плічко, Л.В. (Science-based technologies, 2018)
The analysis of the legislative norms of water quality in Ukraine and the countries of the European Union (EU) is carried out. Propose introducing geoinformation systems (GIS) and remote sensing technology for preventing or reducing water pollution. The main principles of the implementation of the decision-making strategy for water protection activities of surface waters are given. Approaches to the creation of a database of surface water monitoring using GIS and remote sensing technologies are presented. Increasing the quality of water can be achieved through the introduction of new modern technologies to harmonization of the national regulatory base and standards of developed countries, in particular the EU and world health organization (WHO). And also to identify changes in the ecosystem, the prediction of development of dangerous natural and natural-technogenic processes.